On the matter of phytoplankton: A novel method using 3D computer models to calculate biovolume of microorganisms. (22nd March 2021) - Mohan, Joseph; Saros, Jasmine; Stone, Jeffery R.
Abstract: We develop a new method that allows for more accurate biovolume calculations of microorganisms. This method also allows the volume of individual skeletal features of microorganisms to be analyzed separately so that estimates of the resource cost per evolutionary adaptations may be assessed. We also provide a means to link community changes to alterations in nutrient cycles, ecosystem function, and rock‐forming processes by plankton. This method integrates computer‐aided design software from engineering and architecture into biological applications. Our method substantially improves the accuracy of biovolume estimates for species which currently rely upon simple geometric models that preclude the presence of ultrastructure in microorganism skeletons. In addition, using simple shapes to represent the skeletal form of microorganisms prohibits the exploration of resource cost that various adaptations, for example, spines for protection from grazers, have imposed upon plankton. Thus, integrating architectural and engineering approaches more broadly into biovolume estimations produces new insight into the physiology of microorganisms that can turn speculations into quantitative analyses.